Chronic Expanding Hematoma Secondary to Excision of Recurrent Myxomas in a Bitch - Rodríguez-Alarcón, Carlos Arturo; Rivera-Barreno, Ramón; Castro-Arellano, Rene Alejandro; Clark, Marjorie; Toledo-Valdez, Cielo Ana; Staines-Orozco, Hugo Salvador; Beristain-Ruiz, Diana Marcela; Tenreiro Tavares, Inês (Acta Scientiae Veterinariae, 2022)
Background: Expanding chronic hematoma is a relatively common postoperative complication in humans, not in dogs, nevertheless, is important understand this condition because it may affect the animal’s health. A hematoma could be formed within hours and usually stabilizes spontaneously with the reabsorption of its content. However, occasionally the hematoma slowly expands, becomes encapsulated and forms a mass, causing a chronic expanding hematoma. Possibly skin and adipose tissue are displaced secondary to trauma, causing the formation of blood-filled cysts surrounded by a fibrous capsule. The aim of this document is to present the first report of a postsurgical chronic expanding hematoma in dog. Case: A case of chronic expanding hematoma secondary to excision of recurrent myxoma in a bitch was described. Physical examination showed a hard, firm, non-mobile mass enclosed within the deep muscular layers. This mass was between the sternum and the cranial abdomen, similar to previous lesions excised by another veterinarian. Fine needle aspiration indicated the presence of blood. Radiology demonstrated that the bone-cartilage tissue was not involved. Due to the size of the mass, a skin stretching pre-suturing technique using self-adhesive tape was applied around the mass 48 h before surgery. The mass was removed with wide excision margins and portions of the affected muscles, but a large wound with great tension was created; consequently, a parallel to the wound incision and the thoraco-lumbar vertebrae was made. Six months after surgery, the animal presented recurrence of the same lesion, which was also removed. The bleeding times were within the normal range, but the animal was diagnosed with hyperadrenocorticism. After both surgeries histopathological exam revealed a hematoma, that had thrombosis and granulation tissue with fibrosis and severe panniculitis, in addition of multifocal, chronic, moderate lymphohistiocytic myositis; all these changes were compatible with a chronic expanding hematoma. Discussion: Chronic expanding hematoma is a mass that grows slowly secondary to hemorrhage and does not exhibit elements of malignancy. However, it can occasionally be confused for a soft-tissue neoplasm. It has been reported frequently in humans but not in small animals. The first case was reported in 2002: 5 puppies with a cervical hematoma classified as a chronic expanding hematoma was described. In addition, 3 cases were reported: 1 cat with perirenal chronic expanding hematoma; 1 bitch with intra-abdominal presentation, and 1 cat with this pathology on the right pelvic limb after an intramuscular injection. The etiology of chronic expansive hematoma is unidentified in dogs, nevertheless, it is stipulated that is not an inflammatory process as previously assumed, but rather a neoplastic process. As in other cases, it was difficult to determine the origin of the chronic expanding hematoma. The coagulation times and platelets count were within ranges. Similarly, it is very complicated to relate hyperadrenocorticism with chronic expanding hematoma because dogs with Cushing’s disease generally present hypercoagulopathies. Myxomas are associated with endocrinopathies in humans and dogs, therefore, hyperadrenocorticism is possibly related with this neoplasia. Myxomas have an expansive growth pattern, contrasting with myxosarcomas, which are infiltrating; Although in the present case the skin mass appeared to be invasive, both macroscopical and histopathological appearance of it corresponded to a well-shaped capsule compatible with chronic expanding hematoma. In summary, to the best of our knowledge, this is the first report of a post-surgical chronic expanding hematoma in a dog. Keywords: dog, canine, surgery, expanding hematoma, postoperative complications, myxomas, small animal.